An unusual case of diabetic ketoacidosis following salbutamol ingestion in a nondiabetic 13-year-old child - Mai Mustafa; Salma A. Ali (Saudi Journal for Health Sciences)
Salbutamol, a commonly used bronchodilator for managing asthma and other respiratory conditions, can increase blood glucose levels by stimulating glycogenolysis and gluconeogenesis, exacerbating hyperglycemia and raising the risk of diabetic ketoacidosis (DKA). We present a case of a 13-year-old boy with mild asthma who developed DKA after ingesting a salbutamol solution. He presented classic symptoms of DKA, including tachycardia, tachypnea, hypotension, and laboratory findings consistent with metabolic acidosis, hyperglycemia, and electrolyte imbalances. He received supportive care, including fluids, insulin, and close monitoring and showed gradual improvement. He was discharged in good condition with appropriate follow-up instructions. This case stresses the need to recognize salbutamol toxicity as a potential cause of DKA. Healthcare providers should be cautious and avoid unnecessary bronchodilator therapy for patients with metabolic acidosis and breathing difficulties. Patients and caregivers should also be educated about the risks of using salbutamol and the importance of following prescribed dosages.